Preparation of a novel lysozyme molecularly imprinted polymer using uniformly sized functionalized poly(glycidyl methacrylate) microspheres as the matrix and its application to lysozyme purification. (25th October 2013) - Zhang, Jing; Tian, Yong‐le; Wang, Ling‐ling; Han, Yan‐ting
ABSTRACT A novel lysozyme imprinted polymer based on uniformly sized functionalized poly(glycidyl methacrylate) microspheres has been synthesized in aqueous solution using the surface imprinting technique. The microspheres were modified with hydroxyl ethyl methacrylate to allow for the introduction of polymerizable double bonds, with β‐cyclodextrin and acrylamide being grafted onto the surface as functional monomers. The selective recognition properties of the resulting molecularly imprinted polymers (MIPs) were investigated by HPLC. Various factors were also investigated in terms of their influence on the retention behaviors of the imprinted polymers, including the pH and salt concentration of the mobile phase. The binding capability properties of the MIPs were evaluated, and the PGMA/EDMA‐MIPs showed a high adsorption capacity for lysozyme. Furthermore, this MIP was used to separate and enrich lysozyme from egg whites. The results revealed that the lysozyme surface‐modified MIP could be used to efficiently separate and purify lysozyme from egg whites. Copyright © 2013 John Wiley & Sons, Ltd.